If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 3 = 7b + -9 Reorder the terms: 3 + 8b = 7b + -9 Reorder the terms: 3 + 8b = -9 + 7b Solving 3 + 8b = -9 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. 3 + 8b + -7b = -9 + 7b + -7b Combine like terms: 8b + -7b = 1b 3 + 1b = -9 + 7b + -7b Combine like terms: 7b + -7b = 0 3 + 1b = -9 + 0 3 + 1b = -9 Add '-3' to each side of the equation. 3 + -3 + 1b = -9 + -3 Combine like terms: 3 + -3 = 0 0 + 1b = -9 + -3 1b = -9 + -3 Combine like terms: -9 + -3 = -12 1b = -12 Divide each side by '1'. b = -12 Simplifying b = -12
| -1x-10=1.25+0.25 | | 3x+2+2+x=2x+1 | | F=.5k(d-n) | | 3y-5=-10-4y | | -6(3X+2)-13=6 | | 9(3x+1)=4x-5 | | 73-x=28 | | .2x+3=-17 | | 2x-5(4-x)=7+5x | | -84=-7(6-x) | | 4n+2=-2n-10 | | 264=-27 | | 14=7y-bx | | -9p+3+4p+7p-4p-4p= | | -4(6x+2)=6x+22 | | -6(9X+7)=6 | | 2x+12+4=x+16 | | -21y+2=24y-16 | | 12x^2+9x-4=0 | | 2(4)x+2(5)y=118 | | 20+5c=-5 | | 8m-5=35-2m | | 40=5(3x-10) | | 24x+36=0 | | .2x-3=-17 | | -n-24=n+16 | | J=mdy | | 8*x+9=4*x-23 | | 2y-11=-2(y+10) | | 195=55+(15+9)w | | n^2-18n-63=0 | | 6x=6(4+5x) |